(untitled) (The Review of Diabetic Studies, 2024)
Infection control and safety practices are fundamental to guaranteeing excellent healthcare provision and protecting patients and healthcare workers workers. Nursing and dental care settings present shared and unique risks for healthcare-associated infections (HAIs) due to frequent patient contact, exposure to blood and body fluids, and the use of invasive and aerosol-generating procedures. Recent evidence from Saudi Arabia and other regions underscores continuous gaps in infection control knowledge, compliance, and occupational safety among nursing and dental professionals. This review analyzes infection control and safety practices in nursing and dental care settings from an interprofessional perspective, focusing on standard precautions, occupational hazards, education and training, and joint safety culture. Strengthening interprofessional infection control strategies are vital for reducing HAIs, boosting patient safety, and supporting workforce well-being.